Entrepreneurship through employee mobility, innovation, and growth - Salomé Baslandze (Federal Reserve Bank of Atlanta, 2022)
Firm-level productivity differences are big and largely ascribed to ex-ante heterogeneity in the entrepreneurs' growth potential at birth. Where do these ex-ante differences come from, and what can the policy do to encourage the entry of high-growth entrepreneurs? I study empirically and by means of a quantitative growth model the spinout firms: the firms founded by former employees of the incumbent firms. By focusing on innovating spinouts identified through the inventor mobility in the patent data, I document that spinout entrants significantly outperform regular entrants throughout their life. Firms with a bigger technological lead spawn more successful spinouts. Building on these observations, I build a structural model of innovation and firm dynamics, where firm heterogeneity arises from endogenous decisions of innovation workers to become entrepreneurs and create spinouts. The spinout dynamics affect productivity growth through four main channels: direct entry, incumbents' disincentive effect, knowledge diffusion, and the firm composition channel. Growth decompositions show that accounting for spinout dynamics is quantitatively important for our understanding of the growth process. I analyze the role of noncompete laws affecting employee entrepreneurship for aggregate innovation and growth.
Keywords: O30; O43; 330; innovation; spinouts; entrepreneurship; noncompete laws; firm dynamics